Process Evaluation of the Comprehensive Communities Program in Selected Cities in the United States, 1994-1996 - Kelling, George L. ([Verlag nicht ermittelbar], 2009)
This study was a process evaluation of the Comprehensive Communities Program (CCP) intended to develop insights into how community approaches to crime and drug abuse prevention and control evolved, to track how each site implemented its comprehensive strategy, to determine the influence of preexisting ecological, social, economic, and political factors on implementation, and to monitor the evolution of strategies and projects over time. Intensive evaluations were done at six CCP sites: Baltimore, Maryland; Boston, Massachusetts; Columbia, South Carolina; Fort Worth, Texas; Salt Lake City, Utah; and Seattle, Washington. Less intensive evaluations were done at six other CCP sites: Gary, Indiana; Hartford, Connecticut; Wichita, Kansas; the Denver, Colorado, metropolitan area; the Atlanta, Georgia, metropolitan area; and the East Bay area of northern California. At all 12 sites, 2 waves of a Coalition Survey (Parts 1 and 2) were sent to everyone who participated in CCP. Likewise, 2 waves of the Community Policing Survey (Parts 3 and 4) were sent to the police chiefs of all 12 sites. Finally, all 12 sites were visited by researchers at least once (Parts 5 to 13). Variables found in this data collection include problems facing the communities, the implementation of CCP programs, the use of community policing, and the effectiveness of the CCP programs and community policing efforts.